Faktor Determinasi Risk Aversion dan Perilaku Tenaga Kerja Pada Produk Asuransi - affandi, affandi (Prodi Manajemen Zakat dan Wakaf, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Langsa, 2022)
Purpose—The purpose of this article is to try to look at the risk aversion determination factors that encourage the behavior of the educated workforce using or not using insurance products. The indicators used are income, education level, number of Dependents, Gender, employment status, place of residence, generation group, insurance product information Method—The analysis model used is probit regression. Primary data obtained through a survey of 111 respondents and only 93 educated workers in Aceh Province met the specifications and filled in completely. Research Results—The results show that only employment status has a positive and significant effect on labor preferences for insurance products, while other factors are not significant. Limitations — This research is still limited in samples, factors that are used as objects of research and less in-depth about the role of information affecting people's behavior. This is a suggestion for researchers to further conduct more comprehensive research. Practical Implications—The results of this study can be used as a reference for the government and companies must synergize with each other in planning insurance programs. High-income workers are expected to join insurance programs, mutual care is an important social capital to maintain the economy. The government or insurance company must increase the socialization of information on the importance of insurance programs to deal with the uncertainty of future risks.